Perbedaan efektivitas model partisipatif dengan model discovery learning terhadap hasil belajar matematika di Madrasah - Ramdhayani, Ayu; Pardi, M. Habib Husnial; Mauliddin, Mauliddin (LP2M STAI Darul Kamal NW Kembang Kerang, 2021)
Abstract The purpose of this research is to find out whether there is a difference in effectiveness between the participatory model and the discovery learning model on students' mathematics learning outcomes at SMPN 21 Mataram on the subject of circles. This research is a type of experimental research with the static group pretest-posttest design. The sample in this study was class VIII students of SMPN 21 Mataram. The sampling technique in this study was purposive sampling with circle material. The process of collecting data researchers used interviews, observations, and tests as instruments. From the research results, the participatory model of learning outcomes obtained an average pretest score of 58.68 and a posttest average score of 73.32. While the discovery learning model for learning outcomes obtained an average pretest score of 58.86 and a posttest average score of 73.91. The results of the learning outcomes hypothesis test found that the sig. (2-tailed) 0.821. Because the sig value > 0.05, meaning that H0 is accepted and H1 is rejected, it can be concluded that there is no significant difference in effectiveness between the participatory model and the discovery learning model on the mathematics learning outcomes of class VIII students of SMPN 21 Mataram